Studying some anatomical characteristics of four different of variety of bean plant and estimating the percentage of infection with an insect black bean Aphis fabae Scopoli - Wedad M. Hamood / Jinan M. Kalaf ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The study was carried out at the Palm Research Center of Basrah for the purpose of studying the anatomical and histological changes of leaves of bean plants un infected and infected leaves of four variety of bean plant with black bean insect (the Iraqi local variety , the Egyptian variety ,the Syrian variety ,and the Spanish variety ). The results showed differences between the un infected and infected leaves of the four varieties in the thickness of tannin cells, mesophyll , the thickness of the upper and lower epidermal layer , the vascular bundles , and the thickness of the parenchyma cells. There were significant differences in the infection percentage between the months as it was highest in march amounted to 32.33% and the lowest percentage was in January amounted to 17.23%,also the results showed that there were significant differences between the varieties in the rate of infection as the highest rate was in the Syrian variety amounted to 45.96% followed by the Egyptian , Iraqi and Spanish variety ,amounted to 37.45 ,12.44,3.85% respectively.